2016
DOI: 10.18632/oncotarget.8699
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of microRNA signatures for detecting pancreatic malignant transformation in endoscopic-ultrasound guided fine-needle aspiration biopsies

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is a lethal disease. Novel biomarkers are required to aid treatment decisions and improve patient outcomes. MicroRNAs (miRNAs) are potentially ideal diagnostic biomarkers, as they are stable molecules, and tumour and tissue specific.ResultsLogistic regression analysis revealed an endoscopic-ultrasound fine-needle aspiration (EUS-FNA) 2-miRNA classifier (miR-21 + miR-155) capable of distinguishing benign from malignant pancreatic lesions with a sensitivity of 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, How et al (2015) reported that a prognostic 9-mi-RNA signature set for cervical carcinoma identified in frozen samples could not be validated in an independent cohort of FFPE samples and that concordance between frozen and FFPE samples was lacking. A 2-miRNA classifier (miR-21 + miR-155), validated in small cohorts of EUS-FNA and FFPE needle biopsies, exhibited 81.5% sensitivity and 85.7% specificity in distinguishing pancreatic cancer from benign pancreatic lesions (Frampton et al 2016). Kakimoto et al (2016) reported that mi-RNA stability in FFPE tissue correlated with guanine and cytosine (GC) content: GC-rich mi-RNAs were less degraded than those with < 40% GC content.…”
Section: Microrna (Mi-rna)mentioning
confidence: 99%
“…Furthermore, How et al (2015) reported that a prognostic 9-mi-RNA signature set for cervical carcinoma identified in frozen samples could not be validated in an independent cohort of FFPE samples and that concordance between frozen and FFPE samples was lacking. A 2-miRNA classifier (miR-21 + miR-155), validated in small cohorts of EUS-FNA and FFPE needle biopsies, exhibited 81.5% sensitivity and 85.7% specificity in distinguishing pancreatic cancer from benign pancreatic lesions (Frampton et al 2016). Kakimoto et al (2016) reported that mi-RNA stability in FFPE tissue correlated with guanine and cytosine (GC) content: GC-rich mi-RNAs were less degraded than those with < 40% GC content.…”
Section: Microrna (Mi-rna)mentioning
confidence: 99%
“…More recently, next‐generation sequencing (NGS) of DNA, miRNA, and proteomic and metabolomic approaches were evaluated to identify possible biomarkers in cyst fluid in the hopes of improving the diagnostic capability of PCL . A study by Singhi et al .…”
Section: Eus‐fna For Differential Diagnosis and Detection Of Malignanmentioning
confidence: 99%
“…Aspirated cyst fluid occasionally does not contain enough PCL cellular material. A meta-analysis of EUS-FNA for diagnosing PCL, including 18 studies and a total of 1438 patients, showed a pooled sensitivity and specificity of cytological diagnostic capability for differentiating mucinous from non-mucinous cysts as 54% (95% CI, [49][50][51][52][53][54][55][56][57][58][59] and 93% (95% CI, 90-95), respectively. 40 A recent systematic review for the detection of malignant IPMN, including 193 studies with 12,297 patients, showed cyst fluid cytology as area under the curve of 0.84, sensitivity of 54% and specificity of 91% to identify malignant IPMN.…”
Section: Eus-fna For Differential Diagnosis and Detection Of Malignanmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a recent analysis of miRNA expression in 55 endoscopic ultrasound-guided fine needle aspiration biopsies found that miR-21 and miR-155 levels could be used to differentiate malignant from benign lesions with a greater accuracy than standard pathology. However, comparison with other biomarkers (such as CEA) was not possible [80]. Another clinical challenge is making a differential diagnosis between PDAC and bile duct cancers.…”
Section: Ncrnas As Diagnostic Biomarkersmentioning
confidence: 99%